Calculation Of The Torque Of The Rotary Shaft - E.Kh. Nematov; N.O. Kalandarov (Genius Journals, 2023)
The principle of grinding the core on rolls lies in the peculiarities of the interaction of a particle with a pair of rolls rotating towards each other